Production Of Betalain Compounds From Dragon Fruit Hylocereus Costaricensis In Vitro Plant Cell Culture Systems - Winson, Koe Wei Sheng (2020)
Hylocereus costaricensis more popularly known as the purplish-red pitaya or dragon fruit belongs to the Cactaceae family and is one of the next promising biocolourant because of its abundance in betalain compounds. The primary objectives of this study are to induce callus, improve the callus proliferation and enhance betalain content through in vitro means. Axenic seedlings of H. costaricensis were raised in half-strength MS medium, supported on 5 g/L agarose and cultured under the cool white fluorescent lights. In the preliminary study on callus induction, epicotyl and cotyledonary segments of two-month-old axenic seedlings were examined for their callus induction potential when supplemented with various concentrations of NAA and TDZ. The effects of illumination (16-h photoperiod and darkness) on callus induction were also investigated. Generally, cotyledonary explants cultured under 16-h photoperiod was optimum for callus induction. Under the influence of NAA, compact callus with roots were formed while in TDZ supplemented medium formed granular callus. Different concentrations and combinations of picloram and 2,4-D were tested for the induction of friable callus. Picloram at 10 μM picloram induced friable callus with substantial callus biomass. The growth index of callus in half-strength MS medium supplemented with 10 μM picloram was 2.1-fold and 3-fold greater compared to 5 μM picloram + 10 μM 2,4-D and 25 μM picloram respectively in the third subculture cycle, therefore optimum for the proliferation of callus.